Option values of quantity flexibility in nuclear fuel long-term contracts: an application of the least squares Monte Carlo. Issue 2 (3rd March 2020) - Park, Hojeong; Jang, Heesun
ABSTRACT: One of the important features in uranium contracts is that the quantity flexibility option is included in long-term contracts, so that buyer has the flexibility to increase or decrease the quantity purchase and adjust the delivery month depending on the market conditions. While it is important to address the value of the flexibility in the contracts, the literature on the contract valuation in uranium markets is scant. In this paper, we evaluate the quantity flexibility in the context of Korean long-term uranium contracts. Specifically, we adapt the least squares Monte Carlo method to simulate the contract value while incorporating the characteristics of option structure and the dynamics of uranium prices. Our simulation results show that the quantity flexibility can play an important role in uranium long-term contracts. The results are also robust to the choice of basis functions, which implies that the method we applied in this paper could provide correct valuation of long-term contracts. Moreover, our results provide some policy implications related to first, the KHNP's strategy to mix of long-term and spot-market uranium contracts, and second, correct valuation of contract parameters when negotiations take place.